Model Konseling Kelompok Menggunakan Teknik Psikodrama untuk Meningkatkan Kepercayaan Diri Siswa - Dewi, Ratna Sari; Sucipto, Sigit Dwi; Puriani, Risma Anita (Jurnal Fokus Konseling, 2018)
This study aimed to see the effectiveness of group counseling service model using psychodrama technique to improve the self-confidence of students at SMP N 1 Indralaya. This study used a quantitative research method which is Quasi-Experiment. To measure the effectiveness of group counseling service model using psychodrama technique to improve the self-confidence of grade VII students at SMP Negeri 1 Indralaya. The design used is the researcher is pre-experimental: one group pretest-posttest design. The Wilcoxon test results also show the group counseling model using the psychodrama technique developed effectively to improve the student self-confidence by 0.005, because the value 0.005 <0.05, it can be concluded that there is a difference between pretest-posttest, so it can be concluded that there is an influence on the use of psychodrama technique method in group counseling to self-confidence.Keywords:Â  group counseling, psychodrama techniques, self-confidence.